Interpolation of Linear Operators on Orlicz and BMO function spaces - Robertson, Andrew Marcus (My University, 1976)
This thesis is concerned with the study of interpolation theorems involving certain Orlicz spaces and spaces of functions of Bounded Mean Oscillation. In addition, we consider the Orlicz spaces in a weighted sense by applying weight functions satisfying certain growth conditions.
Keywords: Mathematics; Mathematics